Advances and Trends in Chemically Doped Graphene. Issue 24 (11th October 2020) - Ullah, Sami; Shi, Qitao; Zhou, Junhua; Yang, Xiaoqin; Ta, Huy Q.; Hasan, Maria; Ahmad, Nasir Mahmood; Fu, Lei; Bachmatiuk, Alicja; Rümmeli, Mark H.
Abstract: Chemically doped graphene materials are fascinating because these have different desirable attributes with possible synergy. The inert and gapless nature of graphene can be changed by adding a small number of heteroatoms to substitute carbon in the lattice. The doped material may display superior catalytic activities; durable, fast, and selective sensing; improved magnetic moments; photoresponses; and activity in chemical reactions. In the current review, recent advances are covered in chemically doped graphene. First, the different types of heteroatoms, their bonding configurations, and briefly their properties are discussed. This is followed by the description of various synthesis and analytical methods essential for assessing the characteristics of heterographene with specific focus on the selected graphene materials of different dopants (particularly, single dopants, including N, B, S, P, first three halogens, Ge, and Ga, and codopants, such as N/O), and more importantly, up‐to‐date applications enabled by the intentional doping. Finally, outlook and perspectives section review the existing challenges, future opportunities, and possible ways to improve the graphitic materials. The goal is to update and inspire the readers to establish novel doped graphene with valuable properties and for current and futuristic applications. Abstract : Elemental doping is an important aspect to effectively redesign graphene's properties which are attractive for a number of applications. For example, CO2 sensing and cancer detection/treatment. This review article is focused on the different doping aspects of graphene, recent synthetic approaches for the material and up‐to‐date application developments.